Analisis Pengelolaan Anggaran dan Pengembangan UMKM Pada Usaha Produksi Minuman Lokal (Tuak) Di Desa Lamika - Kian, Yorianus Rivarno Kopong; Rengga , Andreas; Romario , Fransiscus De (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2025)
This research aims to analyze budget management and MSME development in the local palm wine production business. The method used in this research is qualitative. The data sources used in this research are primary data and data collection techniques through interviews. The results of this research show that budget management and MSME development in Lamika Village cannot be said to be perfect. This is because the budget management in the palm wine production MSME in Lamika Village is still carried out simply, where income and expenses are recorded or noted without using formal bookkeeping. Business development and marketing of palm wine products currently still rely on word-of-mouth systems. Business actors have not optimally utilized digital technology such as social media and e-commerce to expand market reach.